IDENTIFYING NON-ENGLISH DEPARTMENT STUDENTS’ WEAKNESS POINTS ON COMMONLY FOUND EPT GRAMMAR PROBLEMS (A STUDENTS’ NEEDS ANALYSIS) - Afifa S. Zulfikar (Universitas Pesantren Tinggi Darul Ulum Jombang, 2014)
Abstract The EPT test is a test that measures the academic English proficiency of a non-native speaker of English. This research is aimed at identifying the students‟ weakness points on commonly found grammar problems in EPT. The identification is then used as the basis for constructing a syllabus that meets the students‟ need. In general, the students‟ needs based on the analysis are as follows: 1. Incomplete sentences: conjunctions, comparisons, subject missing, adjective clauses, 2. Underlined words: count/non-count nouns, banana rule, adjectives, prepositions, noun-pronoun agreement, singular/plural nouns; 3. Reading Comprehension and Vocabulary: References, passage organization, exception, inferences, topics, main ideas. Keywords: EPT, students‟ needs, grammar problems Abstrak Tes EPT adalah sebuah tes standar bahasa Inggris yang mengukur kemampuan berbahasa Inggris akademik para petutur non bahasa Inggris. Penelitian ini bertujuan untuk mengidentifikasi kelemahan-kelemahan siswa pada masalah-masalah umum tata bahasa yang sering ditemukan di EPT. Identifikasi tersebut kemudian digunakan sebagai dasar untuk membangun sebuah silabus yang memenuhi kebutuhan siswa. Secara umum, kebutuhan siswa berdasarkan analisis yang telah dilakukan adalah sebagai berikut: 1. Incomplete sentences: conjunctions, comparisons, subject missing, adjective clauses, 2. Underlined words: count/non-count nouns, banana rule, adjectives, prepositions, noun- pronoun agreement, singular/plural nouns; 3. Reading Comprehension and Vocabulary: References, passage organization, exception, inferences, topics, main ideas. Kata kunci: EPT, kebutuhan siswa, masalah tata bahasa